Instructor Leadership in Online Learning: Predictive Relationships Between Servant Leadership and the Community of Inquiry Framework - Sally Meech; Adrie A Koehler (Online Learning, 2024)
Instructor leadership is widely recognized as essential for facilitating meaningful online learning in higher education. While previous studies have applied organizational leadership theories to the study of instructor leadership, fewer studies have investigated online instructor leadership. This predictive correlational study detailed the associations between the Community of Inquiry (CoI) framework and servant leadership (SL) theory and employed multiple regression analyses to investigate the predictive relationships of seven SL dimensions on the three CoI presences. Survey data were gathered from 148 graduate students enrolled in online courses in education, communication, and engineering master’s degree programs using the CoI Survey (Arbaugh et al., 2008) and the SL-28 (Liden at al., 2008). The findings revealed a positive and highly significant correlation between the instruments. The predictive model as a whole explained 66% of the variance in students’ perceptions of a CoI. Three SL predictor variables demonstrated the most influence: helping subordinates grow and succeed, conceptual skills, and creating value for the community. Additional analyses at the CoI subscale level revealed that the SL variables accounted for 73% of the variance in teaching presence, 55% of the variance in cognitive presence, and 31% of the variance in social presence. Implications and limitations are discussed and recommendations are proposed to implement online instructor SL.